PEMANFAATAN CERITA ANAK SEBAGAI ALTERNATIF BAHAN PEMBELAJARAN APRESIASI SASTRA DI KELAS III SEKOLAH DASAR - Mochammad Sultoni (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
Learning appreciation of literature in elementary schools (SD) requires learning materials that are in accordance with the characteristics of elementary school students. Literary appreciation learning materials in addition to having to pay attention to children's development must also consider the elements in the literary work itself, which includes aspects of the form and aspects of content. The selection of materials for learning literary appreciation in elementary schools can be done by utilizing children's stories in children's mass media and children's story books. The use of children's stories as material for learning literature appreciation in elementary schools is reflected in the learning strategies designed by the teacher, namely in the selection of the types of learning activities and the preparation of steps for teaching and learning activities.